Determinants of the palm oil industry productivity in Indonesia - Tina Herianty Masitah; Maman Setiawan; Rina Indiastuti; Adhitya Wardhana (Cogent Economics & Finance, 2023)
This paper investigates total factor productivity growth (TFPG) and its determinants in the Indonesian palm oil sector industries. TFPG is estimated using a growth accounting method. This paper applies the fixed effects model to investigate the determinants of the TFPG. The data is sourced from a manufacturing survey of the Indonesian Bureau of Central Statistics (Badan Pusat Statistika/BPS) for the period 2000-2017. This paper finds that the TFPG of the Indonesian palm oil industry is relatively low. Moreover, output growth, output per worker, export activity, and wages per worker have significant effects on the TFPG. The effect of output growth, which is dominated by the large use of inputs, raises concerns in the aspect of environmental sustainability due to uncontrolled land expansion.
Keywords: 330; growth accounting; Indonesian palm oil industry; output growth; total factor productivity growth